Differentiated Instruction in Inclusive English Classrooms: an Umbrella review (Journal of Educational Sciences, 2026)
In inclusive educational settings, learners exhibit diverse levels of readiness, abilities, and learning preferences, necessitating the use of flexible and adaptive instructional approaches. This umbrella review synthesizes evidence from systematic reviews and meta-analyses examining the effectiveness of Differentiated Instruction (DI) in inclusive English language classrooms. This study aims to analyze how differentiated instruction-encompassing content, process, product, and learning environment-affects students’ learning outcomes in inclusive English classrooms. Methodologically, the study adopts an umbrella review design conducted in accordance with PRISMA guidelines and the Joanna Briggs Institute (JBI) methodology. Relevant systematic reviews and meta-analyses were retrieved from Scopus, Web of Science, ERIC, and Google Scholar databases and critically appraised to ensure methodological rigor. The findings indicate that differentiated instruction has a positive impact on learners’ grammar, reading, speaking, and writing skills, as well as on student motivation, classroom engagement, and social integration. Content and process differentiation demonstrate the most consistent effects across studies. The value of this study lies in identifying the most effective differentiation strategies for inclusive English language classrooms. The results offer practical implications for teachers, curriculum developers, and policymakers seeking to enhance inclusive and learner-centered English language education. Keywords: inclusive education, differentiated instruction, English language teaching, umbrella review, systematic review.